Comparative study of preparation of hazardous drugs with different closed-system drug transfer devices by means of simulation with fluorescein - Eva González-Haba Peña; Silvia Manrique Rodríguez; Ana Mª Herranz Alonso; Patricia Pérez Castán; Mónica Moreno Gálvez; Irene Iglesias Peinado; María Sanjurjo Saez (Elsevier, 2016)
Objectives: The level of environmental contamination generated during preparation and administration of hazardous drugs using different valve closed-systems and their combinations was compared. The actual impact on the overall time of preparation of cytostatics and the economic cost of the different modalities were also compared. Methods: Comparative study of the preparation of fluorescein mixtures with different modalities of valve closed-system combinations. Environmental contamination was detected in critical points of connection, and in splashes produced at any other points. The main variable was qualitative detection of contamination by splashes through ultraviolet light when modalities with or without a connector were compared. A final number of 160 mixtures were prepared to detect differences of at least 5%. Results: Splashes were produced in 7 preparations without a connector (p = 0.015). No significant differences (p = 0.445) were detected either in the use of a supporting vial spike vs an anchoring spike, or in the ChemoCLAVE® system vs valve systems with Fleboflex® solutions. Contamination at any critical point was produced in all preparations. The use of a supporting vial spike, syringe connector and bag solution with Luer connection was the most efficient modality. Conclusions: A syringe connector is needed to guarantee a closed system. Anchoring spikes do not show higher advantages as compared with supporting vial spikes. Fleboflex® solutions with Luer bags are more efficient than ChemoCLAVE® and show similar safety. However, connections of these closed systems are not leak-tight, and it is therefore important to continue studies of contamination of the different closed system transfer devices